Sons of Baseball: Growing Up with a Major League Dad - Braff, Mark (Rowman & Littlefield Publishers, 2023)
A rare glimpse of professional ballplayers, not as pitchers, hitters, managers, and coaches, but as dads and grandads. Sons of major league baseball players grow up in a unique environment, not only because they are raised in part by professional athletes, but also because they are raised by the game itself. They come of age immersed in the distinct sounds and aromas of baseball. The locker rooms, the cinderblock-lined corridors beneath the stands, the dugouts, and the fields are the playgrounds of their youth. In Sons of Baseball, Mark Braff interviews 18 men who share their exclusive stories, ballpark memories, and the challenges and rewards of having fathers whose talents enabled them to reach the pinnacle of their profession. Each chapter is devoted to one son talking about his experiences, from the poignancy of one son’s disclosure that his dad has not been able to acknowledge his son’s sexuality as a gay man, to the humor of another son absconding with the groundskeepers’ cart in Cleveland. With a foreword by Hall of Famer Cal Ripken Jr. and interviews with the sons of beloved players such as Yogi Berra, Mariano Rivera, Roger Maris, Gil Hodges, and Larry Doby, Sons of Baseball provides a unique, well-rounded perspective on the lives of professional ballplayers and their families.